THE PROGNOSIS OF THE MAIN INDICATORS FOR SIZING THE GLOBAL INSURANCE MARKET - ANA PREDA (Annals of the University of Petrosani: Economics, 2016)
The paper aim is the prognosis of indicators sizing international life insurance market using models autoregressive. The evolution of the volume of gross premiums, insurance density was studied over a period of 15 years. The models that we used for this prognosis were monovariabile models, specific for economic systems, with one input variable and one variable output (SISO). The prognosis of indicators shows that there will be not major fluctuations on the worldwide life insurance market, that it sees not a spectacular future, even the indicators will record a slight decline in the coming years.